#TITLE_ALTERNATIVE# - SELENIA DESI (NIM : 20715035), EVA
Superoxide dismutase was involved in cell protection towards superoxide radicals, facilitatingconversion superoxide radical into oxygen and hydrogen peroxide. This enzyme successfully isolated from Staphylococcus equorum. This SOD has been overexpressed in E. coli BL21(DE3) (rMnSODSeq), and was found in dimeric form and required manganese cofactor for its activity. Dimeric structure contributed in stability and protein activity.This research aimed to increase the rMnSODSeq dimer stability by amino acid substitution at domain that can protect the active site and at the dimer interface. This research was initiated by determined the amino acid substitution site using COOT program. Substitution site from leucine169 to tyrosine (L169Y) and glycine125 to asparagine (G125N) was obtained. Substitution of L169Y and G125N was performed at DNA level by site directed mutagenesis of rMnSODSeq coding region in pJExpress414_sodA. Mutation result was confirmed using sequencing and the result showed that the substitution at leucine 169 to tyrosine and glysine 125 to asparagine has been successfully obtained. Overproduction of native rMnSODSeq and rMnSODSeq mutant was performed at 25 Ã‚Â°C 100 rpm with isopropyl β-D-1-thiogalactopyranoside (IPTG) at final concentration of 1 mM for 5 hours. Cell pellet from native rMnSODSeq and mutant overproduction were obtained from 250 mL luria bertani medium and yielded 1.2 gram and 1.3 gram respectively. Purification of SOD was performed using affinity coloumn chromatography Ni2+-NTA followed by anion exchange chromatography Q-Sepharose. Purification yielded pure protein which has been confirmed by a single band on SDS-PAGE. Native rMnSODSeq and mutant were tested using zimography qualitatively and colorimetri quantitatively. Percent inhibiton of native rMnSODSeq and rMnSODSeq mutant were 17.06 %, 15.66 % and 15.54 % respectively. From thermal shift assay (TSA) experiment, Tm of native rMnSODSeq was 54 Ã‚Â°C and 68 Ã‚Â°C same with the previous study, while Tm of L169Y and G125N were 58 Ã‚Â°C and 54 Ã‚Â°C respectively. The L169Y and G125N substitution showed that these amino acid substitution had no effect in their enzymatic activity but alter the structural stability as compared to native rMnSODSeq.